The Effect of Scheduled Care Companion Program in Primary Nursing care on Patients' anxiety in Cardiac Intensive Care Unit - Fateme Biabani; Samaneh Bagherian; Maryam salmani mood; Hossein Sanaei; Marzieh Helal Birjandi (Mashhad University of Medical Sciences, 2021)
Background: Hospitalization in cardiac intensive care units is always associated with negative consequences such as anxiety for patients. Since the family plays a vital role in the care of hospitalized patients, its positive effects are still questionable.Aim: The present study aimed to investigate the effect of patient companion programmed participation in primary nursing care on anxiety among patients in the cardiac intensive care unit.Method: This study was a quasi-experimental research with pre-and post-test design with a control group. The study population consisted of all eligible patients admitted to the cardiac intensive care unit of Razi Hospital in Birjand, Iran. A total of 48 patients was selected in a control (24) and intervention groups (24) through stratified block randomization with a block size of 4 patients. The patients' companions in the intervention group were allowed to attend the patients as planned for 3 days of 30 minutes and contribute to their clinical primary care. In the control group, the visit was still prohibited. Anxiety was measured in both groups at the beginning and on the third day of the patient's admission using the State-Trait Anxiety Inventory (STAI). Data were analyzed using SPSS software (version 16).Results: The results indicated that anxiety reduced in both groups 3 days after hospitalization, however, this reduction was statistically more significant in the intervention group (p=0.001). The anxiety score in the control group before and after the intervention was not significantly different (P=0.56). but  anxiety score in the intervention group before intervention was 56.29±16.79 which decreased to 46.43± 12.32 after the intervention and paired t-test showed a significant difference (P=0.01).Implications for Practice: The supportive presence of a patient's companion in the cardiac intensive care unit significantly reduces patients' anxiety. Therefore, it is recommended to use the programmed presence and participation of the patient's companion as a non-pharmacological intervention to reduce patients' anxiety by reviewing the sessions.